2019
DOI: 10.1177/0333102419884938
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of headache attributed to ingestion or inhalation of a cold stimulus (HICS): A cross-sectional study

Abstract: Background Headache attributed to ingestion or inhalation of a cold stimulus (HICS), colloquially called ice-cream headache, is a common form of a primary headache in adults and children. However, previous studies on adults are limited due to the small number of patients. Furthermore, most of the subjects in previous studies had a history of other primary headaches. Methods Biographic data, clinical criteria of HICS and prevalence of primary headache were collected by a standardized questionnaire. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(45 reference statements)
0
4
0
2
Order By: Relevance
“…This also accounts for the CPEO subgroup with numerically even a higher rate of nearly 50%. Previous studies reported slightly lower rates but these were still higher than in the general population [15,16]. Thus, migraine can be regarded as a frequent headache subtype of CPEO patients with single and multiple deletions.…”
Section: Discussionmentioning
confidence: 78%
“…This also accounts for the CPEO subgroup with numerically even a higher rate of nearly 50%. Previous studies reported slightly lower rates but these were still higher than in the general population [15,16]. Thus, migraine can be regarded as a frequent headache subtype of CPEO patients with single and multiple deletions.…”
Section: Discussionmentioning
confidence: 78%
“…46 Finally, a recent report found that although there was not a greater risk of migraineurs getting HICS, pain intensity was higher when tension-type headaches and migraines were present. 41 Although the underlying mechanisms of HICS are unclear, it is likely to involve TRPM8, and the above observations suggest that there may be a corollary between cold and migraine pain.…”
Section: Discussionmentioning
confidence: 99%
“…von einigen Sekunden bis einigen Minuten [37]. Zwei epidemiologische Studien fanden, dass etwa 75% der betroffenen Menschen berichten, dass der Kopfschmerz weniger als 30 s anhält [37]. Bei 10% der Patienten dauert der Kopfschmerz länger als 5 min.…”
Section: Beschwerdenunclassified